2006
DOI: 10.1038/sj.npp.1301200
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Corticotropin-Releasing Factor Concentration is Associated with Pain but not Fatigue Symptoms in Patients with Fibromyalgia

Abstract: Previous studies have identified stress system dysregulation in fibromyalgia (FM) patients; such dysregulation may be involved in the generation and/or maintenance of pain and other symptoms. Corticotropin-releasing factor (CRF) is the principal known central nervous system mediator of the stress response; however, to date no studies have examined cerebrospinal fluid (CSF) CRF levels in patients with FM. The relationship between CSF CRF level, heart rate variability (HRV), and pain, fatigue, and depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 47 publications
3
70
1
2
Order By: Relevance
“…One study showed that CRH was elevated in CSF of FMS patients and was associated with pain but not fatigue symptoms (McLean et al, 2006). The increased serum CRH reported in the current study may indicate some level of physical or psychologic stress that may exacerbate FMS symptoms (Geenen et al, 2002;Fischer et al, 2016).…”
Section: Discussionmentioning
confidence: 73%
“…One study showed that CRH was elevated in CSF of FMS patients and was associated with pain but not fatigue symptoms (McLean et al, 2006). The increased serum CRH reported in the current study may indicate some level of physical or psychologic stress that may exacerbate FMS symptoms (Geenen et al, 2002;Fischer et al, 2016).…”
Section: Discussionmentioning
confidence: 73%
“…We speculate that these improvements may be related to an augmentation of parasympathetic tone as a consequence of the daily use of PYD (28) and regular exercise (29). There is now persuasive evidence that FM patients have dysautonomia, as evidenced by results of heart rate variability studies, tilt-table testing (30), and sympathetic skin responses (31)(32)(33)(34). Two common clinical manifestations of dysautonomia are neurally mediated hypotension and postural orthostatic tachycardia syndrome (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The normal circadian rhythm for plasma cortisol level is disrupted in FMS patients as evidenced by elevated plasma concentrations in the evening . Corticotropin-releasing hormone (CRH), the principal central nervous system mediator of the stress response, was elevated in the cerebrospinal fluid (CSF) of FMS patients and was associated with pain but not fatigue symptoms (McLean et al, 2006). FMS is quite common in patients with systemic mastocytosis (Theoharides et al, 2015b), a disorder characterized by a higher number and reactivity of mast cells (MCs) (Theoharides et al, 2015c).…”
Section: Pathogenesismentioning
confidence: 99%